Defect blocking via laterally induced growth of semipolar (1 0 1̅ 1) GaN on patterned substrates. (1st November 2016) - Khoury, Michel; Vennéguès, Philippe; Leroux, Mathieu; Delaye, Vincent; Feuillet, Guy; Zúñiga-Pérez, Jesus
Abstract: Semipolar (1 0  1 ̄  1) GaN thin films with state-of-the-art optical and structural quality have been obtained on silicon substrates by metal organic chemical vapor deposition using a novel defect reduction method. We initially apply a classical patterning approach on Si (0 0 1) 7 ° off substrates to reveal the Si (1 1 1) facets over which the subsequent inclined epitaxy will be carried out. After the growth of AlN, the sample is etched with S F 6 before the GaN growth is done on the same structure. The process has shown to induce the spontaneous formation of a defect blocking layer that substantially reduces the presence of threading dislocations and basal stacking faults. This is confirmed by correlated optical and structural characterizations. Further, a simple model explaining the origin and working-principle of the blocking layer will be discussed.